(untitled) (Research, Society and Development, 2021)
Introduction: Gingival recession is established through several factors and its treatment can be planned integrating surgical procedures with the aid of orthodontic treatment. Methods: In this context, a 36-year-old woman sought dental treatment to realign the right lower central incisor. A localized gingival recession was verified, being related to poor positioning of the root. The patient had undergone previous orthodontic treatment, as well as periodontal surgical treatment, after which there was no success. Results: After the planning of the case, the dental element was reallocated through orthodontic movement and then the periodontal surgical treatment was performed. With the results obtained, the improvement of gingival recession through orthodontic and periodontal surgical treatment is discussed. Conclusions: This clinical report shows that the gingival graft, performed after tooth movement, can increase the probability of good results in reducing root exposure.